ST. YOSEF SEBAGAI TELADAN PELAYAN PASTORAL - Tomas Lastari Hatmoko (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2021)
St. Joseph in the Catholic Church has a special place as a protector of the universal Church. Coinciding with the Covid-19 pandemic crisis and the celebration of St. Joseph, the Apostolic Letter